Study on Crushed-Stone Cementation Properties and Bottom Stope Stability of Goaf by Open Stope Mining in Inclined Ore Bodies - Qinqiang Guo; Wenbing Guo; Weiqiang Yang; Longxiang Li; Chaoqun Hu (Applied Sciences)
The mining of the part of the inclined ore body below a goaf is crucial for improving resource extraction and safe production. In this study, the cementation properties of crushed stone during the mining of the inclined ore body were investigated by means of laboratory experiments, theoretical analysis, and numerical simulation. Additionally, orthogonal experiments were performed to assess how factors like water–cement ratio, crushed-stone particle size, and cement–sand ratio affect the strength of the grouting concretion body (GCB). Furthermore, the fluidity of the slurry under different ratios was also measured. Considering both the fluidity of the slurry and the strength of the GCB, the optimal ratios of the slurry were determined to be a water–cement ratio of 2.5:1 and a cement–sand ratio of 1:4. This ratio was then used for crushed-stone cementing under the poorest crushed-stone particle size conditions, based on which mechanical parameters were obtained from experiments. Theoretical analysis equated the problem of the grouting range to the width of the plastic zone of surrounding rock, and a conclusion was reached that the width of the GCB should be at least 29 m. The numerical simulation results reveal that among 30 mining rooms formed below the GCB, 24 mining rooms are in a stable state and 6 mining rooms are partially damaged on a small scale. As a whole, the GCB formed by grout filling into the goaf manages to effectively support the stope below, and it is verified that the theoretical calculation method of the width of the GCB is feasible.